The Implementation Of The Semester Credit System Program 2 Year At The State Madrasah Aliyah - Lutfia Nur Anisah; Istikomah (Adabiyah: Jurnal Pendidikan Islam, 2022)
The purpose of this study was to determine the implementation of the 2 year Semester Credit System (SKS) Program at Madrasah Aliyah Negeri Surabaya. This research method is using qualitative research with a descriptive approach. This research uses a type of field research (field research) using data collection methods through observation, interviews and documentation. The results of this study indicate that the 2 year SKS (SKS) Program can be said to be effective, this is evidenced by the service of educators, student academic competence and adequate facilities and infrastructure. In the implementation of Fiqh learning in the 2-year credit program, it has been effective. The lesson plans are described in a learning component that has been prepared by the respective subject teachers. The descriptions are in the form of promissory notes, prota, SK, KD, RPP. Evaluation in the SKS program is by providing intense services to students who have scores below the average while the evaluation in the field of Jurisprudence is carried out in the middle of the semester, namely the Mid-Semester Examination (UTS) and the Final Semester Examination (UAS) using both written and written test techniques. oral test and hands-on practice. For assessment in the field of Jurisprudence, the teacher takes cognitive, affective and psychomotor assessments.